2012
DOI: 10.1177/1479164112442076
|View full text |Cite
|
Sign up to set email alerts
|

The diabetic patient has a higher benefit from infrapopliteal revascularization than the non-diabetic patient: A 10-year retrospective study

Abstract: Crural reconstruction is a suitable method for peripheral arterial occlusive disease to prevent amputation, particularly in diabetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Aggressive revascularization significantly predicted fewer MAEs in the diabetic group but not in the nondiabetic group, which probably indicates that revascularization conferred benefits on those who had more complex angiographic diseases and comorbidities. 13 Some studies reported that CKD was a predictor of bypass graft failure in PAD. 14 In patients with diabetes and PAD, poor renal function was also a significant predictor of amputation or mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggressive revascularization significantly predicted fewer MAEs in the diabetic group but not in the nondiabetic group, which probably indicates that revascularization conferred benefits on those who had more complex angiographic diseases and comorbidities. 13 Some studies reported that CKD was a predictor of bypass graft failure in PAD. 14 In patients with diabetes and PAD, poor renal function was also a significant predictor of amputation or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive revascularization significantly predicted fewer MAEs in the diabetic group but not in the nondiabetic group, which probably indicates that revascularization conferred benefits on those who had more complex angiographic diseases and comorbidities. 13…”
Section: Discussionmentioning
confidence: 99%